Müller's Muscle-conjunctival Resection Combined With Tarsectomy for Treatment of Congenital Ptosis. Issue 6 (November 2019) - Gazit, Inbal; Gildener-Leapman, Juliana; Or, Lior; Burkat, Cat N.; Pras, Eran; Hartstein, Morris E.
Abstract : Purpose: To evaluate the efficacy of Müller's muscle-conjunctival resection combined with tarsectomy for the treatment of congenital ptosis. Methods: A retrospective, noncomparative case series was performed on 38 eyes of 36 patients who underwent Müller's muscle-conjunctival resection combined with tarsectomy for the treatment of congenital ptosis. Age range was 2–25 years (mean: 7.86 years). Follow-up measurements taken up to 4 years after procedure were compared with baseline values. Results: Thirty-six patients presenting with congenital ptosis underwent Müller's muscle-conjunctival resection combined with tarsectomy. All patients had fair-to-good levator function of 5–10 mm. A mean improvement in the margin reflex distance-1 of 2.79 mm ( p value < 0.0001) was noted. All cases except one achieved excellent lid height and postoperative symmetry of the eyelids. Conclusions: Müller's muscle-conjunctival resection combined with tarsectomy is a safe and effective procedure in the treatment of congenital ptosis in patients with moderate-to-good levator function. The surgery is rapid with quick recovery time. No complications were noted. The authors describe a retrospective case analysis of patients who underwent Müller's muscle-conjunctival resection combined with tarsectomy, for the treatment of congenital ptosis with moderate-to-good levator function, demonstrates excellent results.